Understanding police use of force in the United States - Albrecht, James F. (Critical issues and global perspectives ; volume 1: Special topics in policing, 2024)
The use of force by police in many nations has historically come under intense scrutiny by the public and media. This is most apparent in the United States as it relates to police-involved interactions, particularly when a criminal suspect is a member of a minority or underrepresented group. Fueled predominantly by social media and concurrently supported by traditional news reports, a misconception has been portrayed that American law enforcement officials have persistently engaged in brutality and excessive force as the result of endemic institutional racism. On the contrary, empirical data, agency documentation, and criminal justice records have revealed that the use of force by American police officers has been and continues to be extremely rare. Even in the extraordinary instances when a firearm has been used, these police-involved shootings, regardless of the suspect’s race or ethnicity, have been overwhelmingly proven to be legally justified following prosecutorial investigation and/or judicial processes. Analysis has revealed that the majority of individuals shot by police had in fact been White and that less than 2% of suspects had been unarmed. In addition, the unwarranted criticism targeting the police in the United States has had an undesirable impact, often referred to as the “Ferguson Effect,” wherein police officers have drastically restricted proactive investigative and enforcement activities in an effort to avoid public, media, and governmental scrutiny. As a direct result, gun violence and serious crime have dramatically increased in the United States since 2014. This chapter will undertake a comprehensive examination of these phenomena. Accurate and factual analyses of available data and documentation will be conducted that will support the position that the overwhelming and unwarranted criticism of the police has played a predominant role in the dramatic rise in serious and violent crime in many of America’s largest cities for almost a decade.